2010
DOI: 10.1038/nature09623
|View full text |Cite
|
Sign up to set email alerts
|

Structure and control of the actin regulatory WAVE complex

Abstract: Members of the Wiskott-Aldrich Syndrome Protein (WASP) family control cytoskeletal dynamics by promoting actin filament nucleation by the Arp2/3 complex. The WASP relative, WAVE, regulates lamellipodia formation within a 400 kDa, hetero-pentameric WAVE Regulatory Complex (WRC). The WRC is inactive toward the Arp2/3 complex, but can be stimulated by the Rac GTPase, kinases and phosphatidylinositols. We report the 2.3 Å crystal structure of the WRC and complementary mechanistic analyses. The structure shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
680
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 443 publications
(739 citation statements)
references
References 50 publications
29
680
1
1
Order By: Relevance
“…Recent structural studies of WRC indicate that its plasma membrane localisation is mediated by Sra1-Rac1 interactions that would release the SCAR/WAVE VCA domain for Arp2/3 activation (Chen et al, 2010). However, WRC-Rac1 interactions are of low affinity suggesting recruitment and activation of WRC requires additional factors (Davidson and Insall, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent structural studies of WRC indicate that its plasma membrane localisation is mediated by Sra1-Rac1 interactions that would release the SCAR/WAVE VCA domain for Arp2/3 activation (Chen et al, 2010). However, WRC-Rac1 interactions are of low affinity suggesting recruitment and activation of WRC requires additional factors (Davidson and Insall, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Purified mammalian WRC is inactive, but can be activated in buffer by high concentrations of Rac1 (Ismail et al, 2009). The low affinity of Rac1 for WRC (Chen et al, 2010) suggested that additional unknown factors are required to facilitate WRC-dependent actin polymerisation (Davidson and Insall, 2011). We showed that active Rac1 was indeed insufficient for recruitment and activation of the WRC at the membrane in mammalian cell extract (Koronakis et al, 2011).…”
Section: Introductionmentioning
confidence: 89%
“…Rac1 has been shown to activate WAVE proteins through an interaction with the WRC component CYFIP1/ 2 (Chen et al, 2010). In addition, Arf1 has been found to cooperate with Rac1 in activating the WRC (Koronakis et al, 2011).…”
Section: Jmymentioning
confidence: 99%
“…WAVE proteins are intrinsically inactive and exist in a pentameric complex known as the WAVE regulatory complex (WRC), which includes ABI1 or ABI2, NAP1 (also known as NCKAP1) or NCKAP1L, CYFIP1 or CYFIP2 and HSPC300 (Chen et al, 2010;Eden et al, 2002;Ismail et al, 2009;Stradal et al, 2004) (see poster). Rac1 has been shown to activate WAVE proteins through an interaction with the WRC component CYFIP1/ 2 (Chen et al, 2010).…”
Section: Jmymentioning
confidence: 99%
“…PKC has lipid binding modules that require independent binding to phosphatidylinositol-4,5-bisphosphate (PIP 2 ), diacylglycerol (DAG), and Ca 2+ for efficient membrane localization. Similarly, the WAVE complex undergoes a sequence of interactions with GTPases, acidic phospholipids, and PIP 3 before activation (Chen et al, 2010;Kim et al, 2000;Lebensohn and Kirschner, 2009;Prehoda et al, 2000). In both cases, coincidence detection has the effect of producing spatial and temporal specificity, as well as a threshold-like response (Carlton and Cullen, 2005;Lemmon, 2008).…”
Section: Introductionmentioning
confidence: 99%